Policy Implementation of Religious Moderation in Madrasahs - Bustamin Bustamin; Siska Elasta Putri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study aims to analyze and formulate strategies for implementing religious moderation policies in Madrasahs. This study uses a descriptive qualitative research method with a case study approach with research sites in MAN 2 and MTsN 6 Tanah Datar Regency, West Sumatra Province, Indonesia. Data were collected through a documentary study and an in-depth interview. The data were analyzed using an interactive analysis model, beginning with data acquisition, data condensation, data display, and concluding. The results of the study indicate that the implementation of religious moderation in the Madrasah was not properly implemented due to the following reasons: (1) communication that was not carried out intensively and in a structured manner; (2) The aspect of financial resources is not yet available; (3) Standard procedures for implementing religious moderation for Madrasah are not yet available; and (4) the strategy used is not structured and systematic but still seeks strategy formulation. The results of the SWOT analysis reveal 4 strategies that can be selected by the implementer for the implementation of religious facilitation in Madrasahs to be carried out effectively and efficiently. In addition, the strategy is offered as an innovation for the implementation of religious moderation, especially in Madrasahs and in the entire education sector